Measurement of body composition in postpartum South African women living with and without HIV infection - Madlala, Hlengiwe P.; Myer, Landon; Geffen, Hayli; Meyer, Demi; Mendham, Amy E.; Goedecke, Julia H.; Bengtson, Angela M.; Jao, Jennifer; Dugas, Lara R. (Frontiers in Nutrition, 2024)
Background. While several methodologies are available to measure adiposity, few have been validated in sub-Saharan African (SSA) and none in postpartum African women living with HIV (WLHIV). We compared bioelectrical impendence analysis (BIA) and air displacement plethysmography (ADP) against dual x-ray absorptiometry (DXA) in South African women and examined differences by HIV and body mass index (BMI) status. Methods. Lin’s concordance correlation coefficient (CCC) test was used to examine fat mass (FM), fat free mass (FFM) and total body fat percent (%BF) difference between BIA vs DXA, and ADP vs DXA in women living with HIV (n=57) and without HIV (n=25). The Bland Altman test was used to assess mean differences and the direction of bias. Results. The median age was 31 years (IQR, 26-35) and months postpartum were 11 (IQR, 7-16), 44% of the women had obesity. Lin’s CCC for BIA and ADP vs DXA were both 0.80 for %BF and 0.97 for FM, and 0.86 and 0.80 for FFM, respectively. Mean differences (DXA-BIA and ADP estimates) were 0.22 ± 4.54% (p=0.54) and 3.35 ± 3.27% (p<0.01) for %BF, -0.82 ± 3.56 kg (p=0.06) and 1.43 ± 2.68 kg (p=0.01) for FM, -1.38 ± 3.61 kg (p=0.01) and -3.34 ± 2.37 kg (p<0.01) for FFM, respectively. BIA overestimated %BF in WLHIV and underestimated it in women with obesity. Conclusion. Body composition measurements using BIA and ADP correlated well with DXA, thereby providing alternative, safe tools for measuring postpartum FM and FFM in SSA women, including WLHIV.